Work pattern causes bias in self-reported activity duration: a randomised study of mechanisms and implications for exposure assessment and epidemiology. Issue 1 (19th September 2008) - Barrero, L H; Katz, J N; Perry, M J; Krishnan, R; Ware, J H; Dennerlein, J T
Abstract : Background: Self-reported activity duration is used to estimate cumulative exposures in epidemiological research. Objective: The effects of work pattern, self-reported task dullness (a measure of cognitive task demand), and heart rate ratio and perceived physical exertion (measures of physical task demands) on error in task duration estimation were investigated. Methods: 24 participants (23–54 years old, 12 males) were randomly assigned to execute three tasks in either a continuous (three periods of 40 continuous minutes, one for each task) or a discontinuous work pattern (40 min tasks each divided into four periods of 4, 8, 12 and 16 min). Heart rate was measured during tasks. After completing the 2 h work session, subjects reported the perceived duration, dullness and physical exertion for each of the three tasks. Multivariate models were fitted to analyse errors and their absolute value to assess the accuracy in task duration estimation and the mediating role of task demands on the observed results. Results: Participants overestimated the time spent shelving boxes (up to 38%) and filing journals (up to 9%), and underestimated the time typing articles (up to −22%). Over- and underestimates and absolute errors were greater in the discontinuous work pattern group. Only the self-reported task dullness mediated the differences in task duration estimation accuracy between work patterns. Conclusions: Task-related factors can affect self-reported activity duration. Exposure assessment strategies requiring workers to allocate work time to different tasks could result in biased measures of association depending on the demands of the tasks during which the exposure of interest occurs.